Hybrid NOMA–TDMA for Multiple Accesses with Battery Resistance and Circuit Power Consumption - Akmal Khan; Muhammad Haroon; AL-Falahi Maher (International Journal of Scientific Research in Science and Technology, 2025)
This paper examines a multiple-access (MAC) channel where users are powered by batteries with significant internal resistance. Due to this resistance, only a portion of the power drawn from the battery reaches the load, while the remaining power is dissipate as heat, depending on the discharge current. Users also consume continuous circuit power during transmission, with no power consumption when the device is off. We derive the maximum cumulative rates and define the feasible rate regions under different transmission scenarios. In conventional time-division multiple access (TDMA), where users transmit in separate time slots, the optimal aggregate rate is not achieved when internal resistance is present, unlike in ideal battery systems. To address this, we propose a hybrid NOMA-TDMA scheme that combines non-orthogonal multiple access (NOMA) with TDMA, allocating slots for both orthogonal single-user and non-orthogonal joint transmission. Through convex optimization and numerical analysis, we demonstrate that the maximum achievable rate regions of pure NOMA and TDMA are strictly contained within those of the hybrid scheme. The framework is extended from single-user and two-user cases to general multi-user MAC(U≥2), highlighting the trade-off between circuit energy losses and resistive losses. The hybrid NOMA-TDMA approach consistently provides performance gains by balancing these losses and achieving larger feasible rate regions.
Keywords: Multiple Access Channels (MAC); Battery Resistance; Circuit Power Cost; Hybrid NOMA-TDMA; Non-Orthogonal Multiple Access (NOMA); Time Division Multiple Access (TDMA); Power Allocation; Energy Efficiency